Factors Influencing Young People’s Decision to Open Hajj Savings Accounts at Indonesian Sharia Banks: A Theory of Planned Behavior Approach - Maulana Baharsyah, Ibnu (Green Publisher Indonesia, 2026)
This study aims to analyze the influence of attitudes, subjective norms, and behavioral control on the interest of the younger generation in opening a hajj savings account at Bank Syariah Indonesia (BSI) using the Theory of Planned Behavior (TPB) approach. The study used a quantitative method by distributing questionnaires online to 200 respondents, and as many as 188 data that were suitable for processing. The analysis was carried out using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results showed that the variables of attitude and behavior control had a significant positive effect on the interest in opening hajj savings, while subjective norms did not have a significant effect. The research model has an R² value of 0.700 which means that 70% of the variability of interest is explained by the three independent variables. These findings provide implications for Islamic banking to strengthen marketing strategies based on value perception and ease of access for the younger generation.